2020
DOI: 10.1136/gutjnl-2019-319127
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of spermatogenesis and sperm motility by the high-fat diet-induced dysbiosis of gut microbes

Abstract: ObjectiveHigh-fat diet (HFD)-induced metabolic disorders can lead to impaired sperm production. We aim to investigate if HFD-induced gut microbiota dysbiosis can functionally influence spermatogenesis and sperm motility.DesignFaecal microbes derived from the HFD-fed or normal diet (ND)-fed male mice were transplanted to the mice maintained on ND. The gut microbes, sperm count and motility were analysed. Human faecal/semen/blood samples were collected to assess microbiota, sperm quality and endotoxin.ResultsTra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
158
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 66 publications
(121 reference statements)
9
158
0
Order By: Relevance
“…Pilot data from our group confirms a significant positive correlation between serum zonulin production and ME, while a negative correlation exist between these two markers of intestinal permeability and serum testosterone (figure 1, table 1). While neither zonulin nor ME are conclusive for the presence of SIBO, these observations in the context of Ding’s findings,1 certainly support the concept that bacterial overgrowth in the small intestine may trigger an increase in intestinal permeability and ME, which then impairs testicular function 5 6…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Pilot data from our group confirms a significant positive correlation between serum zonulin production and ME, while a negative correlation exist between these two markers of intestinal permeability and serum testosterone (figure 1, table 1). While neither zonulin nor ME are conclusive for the presence of SIBO, these observations in the context of Ding’s findings,1 certainly support the concept that bacterial overgrowth in the small intestine may trigger an increase in intestinal permeability and ME, which then impairs testicular function 5 6…”
mentioning
confidence: 74%
“…We commend Ding and colleagues for their innovative work investigating how high-fat diet-induced changes to the gut microbiome can alter spermatogenesis 1. This link between the gut microbiome and testicular function had earlier been suggested by studies that reported the consumption of probiotic bacteria could improve spermatogenesis and testosterone production in both mice and men 2 3.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, the number of Bacteroides and Prevotella increased significantly. It has been suggested that the spermatogenesis deterioration may be caused by elevated blood endotoxin levels, epididitis and disturbances in gene expression in the testes [55].…”
Section: Intestinal Microbiota Disorders and Male Fertilitymentioning
confidence: 99%
“…We read with great interest the attractive study by Ding N et al ,1 which reported that the dysbiosis of gut microbiota induced by high-fat diet (HFD) was one of the primary causes for the impaired sperm production and motility. It is likely mediated by elevated blood endotoxin, epididymal inflammation and the dysregulation of testicular gene expressions.…”
mentioning
confidence: 99%